2004
DOI: 10.1271/bbb.68.2571
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Abscisic Acid by the Direct PathwayviaIonylideneethane in a Fungus,Cercospora cruenta

Abstract: We examined the biosynthetic pathway of abscisic acid (ABA) after isopentenyl diphosphate in a fungus, Cercospora cruenta. All oxygen atoms at C-1, -1, -1 0 , and -4 0 of ABA produced by this fungus were labeled with 18 O from 18 O 2 . The fungus did not produce the 9Z-carotenoid possessing -ring that is likely a precursor for the carotenoid pathway, but produced new sesquiterpenoids, 2E,4E--ionylideneethane and 2Z,4E--ionylideneethane, along with 2E,4E,6E-allofarnesene. The fungus converted these sesquiterpen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 18 publications
(34 reference statements)
0
26
0
Order By: Relevance
“…Phytopathogenic fungi such as Botrytis cinerea and Cercospora cruenta are known to release large amounts of ABA (Hirai et al 2000;Inomata et al 2004;Siewers et al 2004;Zhang et al 1999). The fungal ABA biosynthetic pathway has been suggested to be different from that in seed plants.…”
Section: Fungimentioning
confidence: 99%
See 1 more Smart Citation
“…Phytopathogenic fungi such as Botrytis cinerea and Cercospora cruenta are known to release large amounts of ABA (Hirai et al 2000;Inomata et al 2004;Siewers et al 2004;Zhang et al 1999). The fungal ABA biosynthetic pathway has been suggested to be different from that in seed plants.…”
Section: Fungimentioning
confidence: 99%
“…The fungal ABA biosynthetic pathway has been suggested to be different from that in seed plants. While plants biosynthesize ABA from farnesyl diphosphate via an indirect pathway (carotenoid pathway), fungal ABA biosynthesis has been proposed to involve direct cyclization of farnesyl diphosphate and subsequent oxidation steps (direct pathway) (Inomata et al 2004;Nambara and Marion-Poll 2005). Recently, genes for the direct pathway have been cloned from B. cinerea (Siewers et al 2004(Siewers et al , 2006.…”
Section: Fungimentioning
confidence: 99%
“…Compound 2 was obtained as a colorless oil with ½a 20 D 2 8.9 (c ¼ 0.23, MeOH). The molecular formula was determined to be C 15 ( 1 H NMR, 13 C NMR, HSQC, HMBC, 1 H-1 H COSY) revealed that compound 2 had a similar basic skeleton as compound 1 ( Table 1). The difference is that the hydroxyl group was at C-3 0 in 1 and at C-4 0 in 2.…”
Section: Resultsmentioning
confidence: 99%
“…Boud. [3] and (2Z,4E )-g-ionylideneacetaldehyde in Cercospora cruenta [50] which has been reported to be a precursor of abscisic acid biosynthesis in fungi [25]. So far they have not been reported in higher plants, but their occurrence in small amounts can also not be ruled out.…”
Section: Biogenetic Considerations For the Structure Of Unidentified mentioning
confidence: 95%
“…2. Hydroxylation at the allylic position in 5-deoxystrigol (3) can occur either without e as in the formation of strigol and orobanchol e or with the migration of the double bond leading to different compounds (10) and (25) (Fig. 6).…”
Section: Biogenetic Considerations For the Structure Of Unidentified mentioning
confidence: 99%